Music Education and Post-Secondary Music Studies in Canada - Bowman, Wayne (Canadian University Music Review / Revue de musique des universités canadiennes)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2000)
This essay questions the efficacy of conventional disciplinary boundaries in post-secondary music studies, boundaries that reductively define music education as a training ground for public school music teachers. Our expectations of music education and its sphere of influence have been far too modest. To the extent we segregate music education from the goals and objectives of music studies more broadly, we neglect our collective responsibility for the musical life of our country. We have focused inwardly, engrossed in our specialties, leaving the design of school music curricula and the fragile environments in which they must compete for survival to the whims of non-musician bureaucrats and politicians. We have been less than successful in our collective obligation to enhance the musical well-being of the country. Changing these circumstances is among our greatest challenges in the decades ahead.